(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This essay examines porfirian diplomatic initiatives through which Mexico sought to acquire greater international presence in Central America and establish checks and balances to control North American hegemony. Toe author examines attempts by Díaz’ diplomatic corps to intensify relations with Guatemala by reinforcing links with other Central American countries. The article narra tes the approaches, negotiations and impressions of Federico Gamboa, the man of letters in charge of negotiations far Mexico in Guatemala during his travels through the nations of the region. Toe difficulties between El Salvador and Guatemala plus those of Nicaragua and Costa Rica, coupled with the resistance to the Mexican representative’s peace initiative by Guatemalan president Manuel Estrada Cabrera, are fundamental factors in the explanation of the failure of this diplomatic mission to Central America.